2021
DOI: 10.3390/toxics9070172
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Investigation of Atmospheric Gaseous Elemental Mercury Transport and Dispersion Around a Chlor-Alkali Plant in the Ossola Valley (Italian Central Alps)

Abstract: We present the first assessment of atmospheric pollution by mercury (Hg) in an industrialized area located in the Ossola Valley (Italian Central Alps), in close proximity to the Toce River. The study area suffers from a level of Hg contamination due to a Hg cell chlor-alkali plant operating from 1915 to the end of 2017. We measured gaseous elemental Hg (GEM) levels by means of a portable Hg analyzer during car surveys between autumn 2018 and summer 2020. Moreover, we assessed the long-term dispersion pattern o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Although the ability of lichens to take up Hg and provide accurate patterns of Hg contamination around emission sources is well documented [ 11 , 19 , 20 , 21 , 22 , 23 , 24 ], information on their ability to reflect the decreasing environmental availability of this element is minimal and contrasting. Walther et al [ 25 ] found an efficient long-term ability of lichens to release the accumulated Hg, as a consequence of the phase-out of the contamination source (a chlor-alkali facility), but Godinho et al [ 26 ] and Vannini et al [ 15 ] reported the lack of long- and short-term release of accumulated Hg over time.…”
Section: Introductionmentioning
confidence: 99%
“…Although the ability of lichens to take up Hg and provide accurate patterns of Hg contamination around emission sources is well documented [ 11 , 19 , 20 , 21 , 22 , 23 , 24 ], information on their ability to reflect the decreasing environmental availability of this element is minimal and contrasting. Walther et al [ 25 ] found an efficient long-term ability of lichens to release the accumulated Hg, as a consequence of the phase-out of the contamination source (a chlor-alkali facility), but Godinho et al [ 26 ] and Vannini et al [ 15 ] reported the lack of long- and short-term release of accumulated Hg over time.…”
Section: Introductionmentioning
confidence: 99%
“…It was also observed that Hg amount in all species (in a range ca. 30–100 ng/g DW) was similar or lower than values reported, e.g., in Usnea from Antarctica (93–199 ng/g DW or 228–387 ng/g DW [ 6 , 9 ]), Hypogymnia from a forest area in Czech republic/Poland (mean value 129 ng/g DW, [ 29 ]), Parmelia from South Africa (60–218 ng/g DW, [ 7 ]), Xanthoria from Italy (50–400 ng/g DW, [ 8 ]) and Parmelia from Italy (142–624 ng/g DW, [ 10 ]), indicating that Hg air pollution is probably not problematic in Slovakia.…”
Section: Resultsmentioning
confidence: 99%
“…Lichens are not plants, but lichenized fungi with their body (thallus) typically formed by the symbiotic association between fungus and green alga. Despite more common works focused on the use of lichens for biomonitoring of metallic pollution including the occurrence of Hg [ 6 , 7 , 8 , 9 , 10 , 11 ], physiological studies are rare [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, allochthonous inputs of terrestrial detritus and plant material may be an important mercury source to stream food webs [ 51 , 52 ]. A recent analysis of atmospheric mercury concentrations around the chlor-alkali plant shows that significant inputs are still deriving from the industrial area [ 53 ]. Thus, the mercury enrichment found in sediments at Prata, located upstream from the industrial plant, may derive from past and present contributions via atmospheric transport, even if the main wind direction is toward the river mouth.…”
Section: Resultsmentioning
confidence: 99%